UPAYA PEMERINTAH MEWUJUDKAN PEMERINTAHAN YANG BEBAS DARI KORUPSI, KOLUSI, DAN NEPOTISME - Deswantara, Yogi Mahendra (DiH: Jurnal Ilmu Hukum, 2012)
Abstrak 18 Paragraph (2) The 1945 Constitution of The Republic of Indonesia, call that The regional authorities of the provinces, regencies and municipalities shall administer and manage their own affairs according to the principles of regional autonomy and the duty of assistance (tugas pembantuan). Organization of local governments led by the head region and assisted by a deputy regional head. In carrying out the duties and authority under Article 25 and Article 26, the regional head and deputy regional heads have an obligation in accordance with Article 27 Paragraph (1) letter (d) The Act Number 32 of 2004 on Regional Government. In this study, only the function of the regional heads in running the regional government was analyzed whether it has been in compliance or not with the norms / rule and standards based on regional autonomy of the regional heads of regional government according to democratic principles , while the deputy head of the area is not discussed.